Trajectories of Early Childhood Developmental Skills and Early Adolescent Psychotic Experiences: Findings from the ALSPAC UK Birth Cohort - Hameed, Mohajer A.; Lingam, Raghu; Zammit, Stanley; Salvi, Giovanni; Sullivan, Sarah; Lewis, Andrew J. (Frontiers in Psychology, 2018)
Objective: The aim of this study was to use prospective data from the Avon Longitudinal Study of Parents and Children (ALSPAC) to examine association between trajectories of early childhood developmental skills and psychotic experiences in early adolescence. Method: This study examined data from n = 6790 children from the ALSPAC cohort who participated in a semi-structured interview to assess psychotic experiences at age 12. Child development was measured using parental report at 6, 18, 30 and 42 months of age using a questionnaire of items adapted from the Denver Developmental Screening Test – II. Latent class growth analysis was used to generate trajectories over time for measures of fine and gross motor development, social and communication skills. Logistic regression was used to investigate associations between developmental trajectories in each of these early developmental domains and psychotic experiences at age 12. Results: The results provided evidence that decline rather than enduringly poor social (adjusted OR = 1.28, 95% CI = 1.10 – 1.92, p = .044) and communication skills (adjusted OR 1.12, 95% CI = 1.03 – 1.22, p = .010) is predictive of suspected or definite psychotic experiences in early adolescence, than those with stable and/or improving skills. Motor skills did not display the same pattern of association; although gender specific effects provided evidence that only declining pattern of fine motor skills was associated with suspected and definite psychotic experiences in males compared to females (interaction OR = 1.47, 95% CI = 1.09-1.97, p = .012) Conclusions: Findings suggest that decline rather than persistent impairment in social and communication skills were most predictive of psychotic experiences in early adolescence. Findings are discussed in terms of study’s strengths, limitations and clinical implications.